Critical Review on Prevention of the Hridroga on the basis of Shat Kriyakala Theory of Ayurveda (AYUSHDHARA, 2024)
Objective: (1) To explore the measures available in the literature for prevention of Hridroga on the basis of Shat Kriyakala the theory of Ayurveda. (2) To develop a general preventive measure through Ayurvedic principles for the prevention of heart diseases. Data source: Classical Ayurvedic textbooks Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, commentaries, modern literature, and research journals available from database PubMed and Google Scholar were searched to interpret the concept of Shat Kriyakala (six stages of disease progression) for the prevention of Hridroga. Review methods: Both Ayurvedic classics and recent research on Hridroga, its risk factors, preventive strategies were explored. Results: Integrating preventive strategies like Nidana Parivarjanam (avoiding causative factors), Dinacharya (daily regimen), Ritucharya (seasonal regimen),Vyayama (regular exercise), Sadvritta (ideal code of conduct) and Yoga and Pranayama at each stage of Shat Kriyakala facilitates early detection, appropriate management, and restoration of homeostasis. Conclusion: By embracing Ayurvedic principles alongside contemporary medical insights, individuals can mitigate cardiovascular risks, enhance well-being, and optimize longevity.